Feasibility of Non-thermal Plasma Assisted Semiconductor Material Synthesis for Thermoelectric, Photovoltaic and Energy Applications - Andrew Ragai Henry, Anak Rigit; Sanaullah, Khairuddin; A., Khan; Javid, W.; Mushtaq, M. U. (IJMMM, 2019)
Silicon being the major component in the semiconductor industry has proved itself very effective in myriad applications that include its use in transistors, energy storage, photovoltaics etc. A boom into its efficiency has emerged with the use of the Nano technology, when the same material is used at Nano scale for the fabrication of the devices in the said applications, it provides promising characteristics. Yet the synthesis techniques for the usage of the silicon as material at Nano scale encounter myriad hurdles, however, still the application of non-thermal plasma at Nano scale has found promising results in this field. It could bring about a huge improvement into its efficiency and can thus become ideal for the vast industrial uses. Yet it encounters several issues that makes this practice economically not feasible, like it needs more time to process such material rather than the conventional methods to synthesize materials on the liquid, solid or gas phases have their own short comings which will result into certain compromises the synthesizers have to deal with based on the properties of the end finished product. On the contras, Non-thermal plasma processing is found cost effective with properties like lack of agglomeration and more efficiency.